Determining the Characteristics of Trips Generated on Southern Bali using Category Analysis - I Wayan Suweda; Achmad Wicaksono; Indrasurya Budisatria Mochtar (IPTEK The Journal for Technology and Science, 2011)
Southern Bali, a tourism center of Indonesia, has been rapidly developed. Unfortunately, the development is not followed simultaneously by the development of adequate transportation network, as a result, traffic congestion are inevitably occurred along every urban road in the district. Therefore integrated development and regional transport planning therefore, is urgently required. In this study, trip generation is determined using Category Analysis. It is Figured out from the household based interview that Denpasar Barat zones are found to have the largest trip generation while Pecatu zones are found to be the smallest. Most of the household trips generated use private vehicles (94.95%) and the rest uses public transport. This also indicates that public transport services in Southern Bali still need to be developed.